POLITIK HUKUM SISTEM REKRUTMEN POLITIK YANG IDEAL BERDASARKAN UDHR & NILAI PANCASILA - Farisi, Mochammad; Harahap, Rahayu Repindowaty; Novianti; Ramlan (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The position of political parties as democratic institutions in Indonesia has a strategic role in producing prospective leaders in the legislative and executive institutions directly elected by the public through elections. However, the Law on Political Parties as the basis for the implementation of recruitment has not been able to produce prospective leaders who are in accordance with the mandate of the 4th principle of Pancasila, which implies the birth of leaders with the characteristics of wisdom and wisdom. Article 29 paragraph (1a); paragraph (2) of the Political Party Law only regulates the recruitment pattern that the selection of candidates for Regional Heads and DPRD candidates is carried out democratically, openly and in accordance with the bylaws of political parties. There are no detailed regulations related to the meaning of the democratic clause, thus creating an oligarchy of party elites, prone to